2023
DOI: 10.3389/fpls.2022.1017282
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Combined effect of Zinc lysine and biochar on growth and physiology of wheat (Triticum aestivum L.) to alleviate salinity stress

Abstract: Globally, Food security main threaten by abiotic stress like salinity and levels amongst the majority serious environmental stressors which reduce crop yield mass production. Biochar application has received much attention in agricultural practices as it enhances crop quality and production. The present study was carried out to analyze the role of lysine zinc and biochar on growth enhancement of wheat (Triticum aestivum L. cv. PU-2011) under saline stress (EC 7.17 dSm-1). Seeds were sown in pots containing sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
(84 reference statements)
2
10
0
Order By: Relevance
“…In this study, semi-coke treatment enhanced antioxidant enzyme activity and showed higher biomass. This aligns with previous research using biochar treatment, which enhanced the activities of SOD, POD, and CAT in plants, reducing oxidative damage [29]. Therefore, the above results support the conclusion that all three types of oil shale waste residues activate antioxidant enzyme activity, alleviating oxidative damage to cell membranes caused by salt stress.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, semi-coke treatment enhanced antioxidant enzyme activity and showed higher biomass. This aligns with previous research using biochar treatment, which enhanced the activities of SOD, POD, and CAT in plants, reducing oxidative damage [29]. Therefore, the above results support the conclusion that all three types of oil shale waste residues activate antioxidant enzyme activity, alleviating oxidative damage to cell membranes caused by salt stress.…”
Section: Discussionsupporting
confidence: 91%
“…One study, for instance, indicated that when the salt (NaCl) concentration was 100 mM, the malondialdehyde content in maize seedlings increased by 310.9% compared to the control [42]. Similar results have been reported in cotton [11], rapeseed [28], tomatoes [10], and wheat [29]. However, all three types of oil shale waste residue treatments reduced malondialdehyde content compared to the control, suggesting the potential alleviation of oxidative damage to cell membranes.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The application of Fe lowered the uptake of Zn as they appeared to have an antagonistic effect in absorption by plants [ 42 , 58 ]. Inhibited upregulation of Fe and Zn transporters might be the major reason behind Fe and Zn deficiency symptoms in salt-stressed plants [ [59] , [60] , [63] ]. In the current study, the external use of Fe plausibly repressed the accumulation of Na by maize tissues and improving the tolerance against salt stress.…”
Section: Discussionmentioning
confidence: 99%